Getting Started with tmux : maximize your productivity by accessing several terminal sessions from a single window using tmux - Quinn, Victor (Community experience distilled., 2014)
The book is intended for software developers, DevOps engineers, and other professionals who make heavy use of the terminal in their daily workflow. Some familiarity with the terminal is useful but no prior experience with tmux or other terminal multiplexers (such as GNU Screen) is required.